Effectiveness of Artificial Wistar Rat Cage Size in Accelerating The Occurrence of Dysplasia in The Process of Formaldehyde Induction - Anak Agung Ayu Niti Wedayani; Kusuma, I Gusti Ketut Artha Jaya; Restuningdyah, Novia Andansari Putri; Wiguna, Putu Aditya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Cage is a medium used in placing experimental animals in experimental-based studies to serve as learning instruments related to studying the cause and effect to be investigated. The size of the cage can affect several health factors in experimental animals, such as the social level and stress level of the animal. Formaldehyde is a carcinogenic compound that can cause malignancies if exposed continuously to living things. Therefore, the purpose of this study was to determine whether cage size can affect the degree of dysplasia in Wistar rats induced by 40 ppm formaldehyde. This study is a quantitative study that uses a true experimental research design with post-test only control group design. This study used male Wistar rats (Rattus norvegicus) with a total of 15 rats divided into 3 groups, namely, a small cage group with a size of (27.5 x 21.5 x 9) cm3, a medium cage group with a size of (28 x 22.5 x 10) cm3, and a large cage group with a size of (30 x 24 x 11.5) cm3 with a total of 4 treatment rats (formaldehyde 40 ppm) and 1 control rat (untreated) in each group. The treatment given to rats was carried out 6 hours per day and lasted for 12 weeks until all rats were terminated at the same time. The rats were terminated and histopathological observations were made to assess the degree of dysplasia that occurred. The results of the Kruskal-Wallis statistical test showed a significant relationship (p < 0.05). This study shows that there is a relationship between the size of artificial cages and the degree of dysplasia in Wistar rats induced by 40 ppm formaldehyde.